Pharmacological Modulation of Neurite Outgrowth in Human Neural Progenitor Cells by Inhibiting Non-muscle Myosin II - Lilienberg, Julianna; Hegyi, Zoltán; Szabó, Eszter; Hathy, Edit; Málnási-Csizmadia, András; Réthelyi, János M.; Apáti, Ágota; Homolya, László (Frontiers in Cell and Developmental Biology, 2021)
Studies on neural development and neuronal regeneration after injury are mainly based on animal models. The establishment of pluripotent stem cell (PSC) technology, however, opened new perspectives for better understanding these processes in human models by providing unlimited cell source for hard-to-obtain human tissues. Here, we aimed at identifying the molecular factors that confine and modulate an early step of neural regeneration, the formation of neurites in human neural progenitor cells (NPCs). Enhanced green fluorescent protein (eGFP) was stably expressed in NPCs differentiated from human embryonic and induced PSC lines, and the neurite outgrowth was investigated under normal and injury-related conditions using a high-content screening system. We found that inhibitors of the non-muscle myosin II (NMII), blebbistatin and its novel, non-toxic derivatives, initiated extensive neurite outgrowth in human NPCs. The extracellular matrix components strongly influenced the rate of neurite formation but NMII inhibitors were able to override the inhibitory effect of a restrictive environment. Non-additive stimulatory effect on neurite generation was also detected by the inhibition of Rho-associated, coiled-coil-containing protein kinase 1 (ROCK1), the upstream regulator of NMII. In contrast, inhibition of c-Jun N-terminal kinases (JNKs) had only a negligible effect, suggesting that the ROCK1 signal is dominantly manifested by actomyosin activity. In addition to providing a reliable cell-based in vitro model for identifying intrinsic mechanisms and environmental factors responsible for impeded axonal regeneration in humans, our results demonstrate that NMII and ROCK1 are important pharmacological targets for the augmentation of neural regeneration at the progenitor level. These studies may open novel perspectives for development of more effective pharmacological treatments and cell therapies for various neurodegenerative disorders.